Relation of elevated serum adenosine deaminase levels to glycated hemoglobin and serum uric acid in type 2 diabetes mellitus - Debes Ray; Dipankar Kundu; Debkanya Gon Chowdhury; Srinika Ghosh; Suparna Dutta; Aninda Dhar (International Journal of Medical Research and Review, 2016)
Background: Adenosine deaminase (ADA) is suggested to be an important enzyme for modulating the bioactivity of insulin, but its clinical significance in Type 2 diabetes mellitus is not yet established. The present study was undertaken to evaluate serum ADA activity and serum uric acid levels in patients of Type 2 DM. It is widely reported that immunological imbalance is one of the key factors associated with the metabolic disturbances in type 2 diabetes mellitus.Aims: The present study aimed to evaluate the serum Adenosine Deaminase level and to correlate ADA levels with Blood Glucose and HbA1c levels in Type-2 Diabetes Mellitus patients.Material and Method: It is a case control study. The subjects included in this study were divided into 3 groups. Group I consisted of 50 normal healthy individuals who served as controls with no history of DM. Group II consisted of 50 patients of Type 2 Diabetes Mellitus both males & females in the age group of 40-65 years on oral hypoglycemic drugs with HbA1c <7%. Group III consisted of 50 patients of Type 2 Diabetes Mellitus both males & females in the age group of 40-65 years on oral hypoglycemic drugs with HbA1c >7 %. Serum levels of fasting blood sugar, HbA1c, ADA and uric acid were estimated in all the subjects under study.Results: All the three parameters, FBS, HbA1c, ADA and serum uric acid levels were found to be increased in the patients of Type 2 DM as compared to controls. The mean serum uric acid levels showed a bell shaped relation with glycemic control.Conclusion: From the present study, it is concluded that there is an increase in serum ADA levels with increase in HbA1c levels. It was found that the serum uric acid levels increased with increasing levels of HbA1c <7% and then decreased with further increasing levels of HbA1c >7% (a bell-shaped relation).